A development and integration framework for optimisation-based enterprise solutions - Pinheiro, Rodrigo Lankaites; Landa-Silva, Dario (Scipress, 2014)
The operations research literature includes some papers describing collaborative work between researchers and industry. However, not much literature exists that outlines methodologies to guide the development of a decision support module and its integration into an existing information management system. Here we describe a framework to aid the collaborative development of an optimisation solution by researchers and information system developers. The proposed framework also helps in the effective integration of the information management system and the decision support module. The framework is divided into three main components: a data model, a data extractor and validator, and a solution visualisation and auxiliary platform. We also describe our experience and positive results from applying the proposed development and integration framework to a project involving the development on an optimisation-based solution for workforce scheduling and optimisation problems. We hope that this contribution would be particularly useful for less experienced researchers and practitioners who embark on a collaborative development of a decision support module based on optimisation techniques.